Antimicrobial biomaterials with non‐antibiotic strategy. Issue 3 (17th September 2019) - Ge, Xiang
Abstract : Biomedical implants have revolutionised medicine, while they also increase the risk of implant‐associated infection which is one of the most frequent and severe complications accompanied by the application of biomaterials. Since the widespread usage of antibiotics drives the emergence of multidrug‐resistant strains, the orthopaedic implant infections are usually hard to treat due to the antibiotic resistance, tolerance and/or persistence of pathogens. Given the growing impact of multidrug resistance, an urgent need has been triggered to develop new types of antimicrobial strategy other than using antibiotics. In this review, the authors highlight the recent progress on antimicrobial biomaterials with non‐antibiotic strategies including chemical strategy, physical strategy, and synergetic strategy. The antimicrobial mechanisms of many kinds of non‐antibiotic antimicrobial biomaterials are still not fully understood. Researchers gradually found that welcoming microbial cellular adhesion to a lethal surface was a more effective solution than targeting microbial cellular repulsion when designing antimicrobial surfaces. Moreover, there is a popular tendency to make the antimicrobial biomaterials not only kill pathogenic microbes but also facilitate the adhesion and growth of the healthy cell, which means that the next generation biomaterials should possess dual functions of preventing microbial infection together with promoting tissue regeneration simultaneously for biomedical applications.